Essential Clinical Global Health, edited by Brett D. Nelson - Thakore, Shefali; McKay, William P (Revue canadienne de l’éducation médicale, 2017)
In the past two decades there has been a more concerted effort to make rational, evidence-based approaches to what has been, for the previous two centuries, a somewhat chaotic mixture of missionary-based, NGO-based, university and United Nations-based efforts at international research and clinical practice in financially poor countries. Essential Clinical Global Health is a welcome new addition to problems of providing good quality health care in resource-limited settings. The emphasis is on poor countries, although some information is useful for remote settings in developed countries.